Comparative out‐of‐hospital mortality of long‐acting opioids prescribed for non‐cancer pain: A retrospective cohort study. Issue 1 (12th July 2018) - Chung, Cecilia P.; Dupont, William D.; Murray, Katherine T.; Hall, Kathi; Stein, C. Michael; Ray, Wayne A.
Abstract: Purpose: Despite significant growth of opioid prescriptions, only limited data are available regarding the comparative safety of long‐acting opioids for chronic non‐cancer pain. Recent data suggest that transdermal fentanyl and oxycodone CR may have greater toxicity than morphine SR in patients with non‐cancer pain. Thus, we compared the risk of out‐of‐hospital deaths in patients with non‐cancer pain filling prescriptions for transdermal fentanyl or oxycodone CR with that for morphine SR. Methods: We conducted a retrospective cohort study in 50 658 patients enrolled in Tennessee Medicaid who filled prescriptions for transdermal fentanyl ( n = 8717), oxycodone CR ( n = 14 118), or morphine SR ( n = 27 823) between 1999 and 2011. We excluded individuals with cancer or other life‐threatening diagnoses and used propensity scores to adjust for multiple potential confounders. The primary outcome was out‐of‐hospital mortality. Results: During 44 385 person‐years of follow‐up, 689 patients died. The out‐of‐hospital mortality rate among all study subjects was 155/10 000 patient‐years. Contrary to earlier data suggesting greater risk, mortality was not significantly different in patients filling prescriptions for transdermal fentanyl compared with morphine SR (adjusted HR = 0.96, 95% C.I.: 0.77‐1.21); moreover, patients filling prescriptions for oxycodone CR had lower mortality risk compared with those filling prescriptions for morphine SR (adjusted HR = 0.79, 95% C.I. 0.66‐0.95). Conclusion: In the study population, long‐acting opioids for non‐cancer pain were associated with high out‐of‐hospital mortality rates. We found comparable out‐of‐hospital mortality risks associated with transdermal fentanyl and morphine SR. The risk of out‐of‐hospital death for oxycodone CR was lower than that for morphine SR.